A World of Difference - Blair, Leona (New York Publisher: Bantam, 1990)
Set in London, Paris and New York from the turn of the century to World War II, this story follows the fortunes of Connor McKenzie, whose fate is interwined with those living at Brandon Hall. Leona Blair's other titles include "With this Ring", "A Woman's Place" and "Privilege".
English Fiction.
Keywords: Romance fiction -- Families -- Fathers and daughters